Conducting conservation social science surveys online. Issue 5 (22nd April 2021) - Wardropper, Chloe B.; Dayer, Ashley A.; Goebel, Madeline S.; Martin, Victoria Y.
Abstract: The coronavirus (COVID‐19) pandemic is affecting the environment and conservation research in fundamental ways. Many conservation social scientists are now administering survey questionnaires online, but they must do so while ensuring rigor in data collection. Further, they must address a suite of unique challenges, such as the increasing use of mobile devices by participants and avoiding bots or other survey fraud. We reviewed recent literature on online survey methods to examine the state of the field related to online data collection and dissemination. We illustrate the review with examples of key methodological decisions made during a recent national study of people who feed wild birds, in which survey respondents were recruited through an online panel and a sample generated via a project participant list. Conducting surveys online affords new opportunities for participant recruitment, design, and pilot testing. For instance, online survey panels can provide quick access to large and diverse samples of people. Based on the literature review and our own experiences, we suggest that to ensure high‐quality online surveys one should account for potential sampling and nonresponse error, design survey instruments for use on multiple devices, test the instrument, and use multiple protocols to identify data quality problems. We also suggest that research funders, journal editors, and policy makers can all play a role in ensuring high‐quality survey data are used to inform effective conservation programs and policies. Abstract : Article impact statement : Online social surveys can provide reliable data to inform conservation through robust sampling and recruitment, testing, and data cleaning. Abstract : Resumen: La pandemia del coronavirus (COVID‐19) está afectando al ambiente y a la investigación para la conservación de maneras fundamentales. Muchos científicos sociales de la conservación ahora están aplicando encuestas en línea, pero lo deben hacer mientras aseguran que hay rigor en la recolección de datos. Además, deben abordar un conjunto de retos únicos, como el incremento en el uso de dispositivos móviles por parte de los participantes y la evasión de bots y otros fraudes en las encuestas. Revisamos la literatura reciente sobre los métodos de encuestas en línea para examinar el estado del campo relacionado con la colección y difusión de datos. Ilustramos esta revisión con ejemplos de decisiones metodológicas importantes realizadas durante un estudio nacional de personas que alimentan a aves silvestres, en el cual quienes respondieron la encuesta fueron reclutados por medio de un panel en línea y una muestra fue generada por medio de una lista de participantes en el proyecto. La aplicación de encuestas en línea brinda oportunidades nuevas para el reclutamiento de participantes, diseños y evaluación de pilotos. Por ejemplo, los paneles de las encuestas en línea pueden proporcionar acceso rápido a muestras grandes y diversas de personas. Con base en la revisión de la literatura y en nuestras propias experiencias, sugerimos que para asegurar la elaboración de encuestas en línea de alta calidad uno debe explicar el error potencial de muestreo y por ausencia de respuesta, diseñar instrumentos de encuesta para su uso en diferentes dispositivos, probar el instrumento y usar múltiples protocolos para identificar problemas con la calidad de los datos. También sugerimos que los financiadores de la investigación, los editores de revistas y formuladores de políticas pueden jugar un papel para asegurar que se usen datos de encuestas de alta calidad para orientar a los programas y las políticas de conservación.